Soyabean Development: a study of its socio-economic impact - Alexander K.C. Kumaran K.P. Rajula Devi A.K. (Hyderabad National Institute of Rural Development, 1993)
Study with special reference to Madhya Pradesh, India.
Keywords: Soybean industry; Farmers-- India -- Madhya Pradesh -- - Economic conditions.--Social conditions -- Case studies